Geothermal industry waste-derived catalyst for enhanced biohydrogen production. (November 2020) - Munfarida, Siti; Widayat,; Satriadi, Hantoro; Cahyono, Bambang; Hadiyanto,; Philia, John; Prameswari, Jedy
Abstract: The main aim of this work was to develop sustainable catalyst from geothermal waste by hydrothermal process for enhanced biohydrogen production. The effects of Si/Al ratio and pH neutralization on the catalyst were also investigated to provide further insight into the hydrogen production capability. Results have shown with increasing Si/Al ratio, a lower amount of catalyst was synthesized and smaller particle size was obtained. pH neutralization treatment resulted in higher conversion compared to non-neutralized ones. Meanwhile, the highest conversion of biohydrogen from ethanol through steam reforming process (95.19%) was obtained from catalyst with pH neutralization treatment and Si/Al ratio of 10. The catalyst developed in this study was concluded to be suitable for framework/supporting catalyst due to relatively low selectivity. Highlights: Catalyst showed promising performance in biohydrogen production. Si/Al ratio and wash treatment was significant to catalyst yield. Si/Al ratio and wash treatment was significant to biohydrogen conversion. Si/Al ratio 10 and wash treatment give highest ethanol-hydrogen conversion, 95.19%. Geothermal waste-derived catalyst was more suitable for framework/support catalyst.